(untitled) (Jurnal Hukum Islam, 2019)
This paper discusses tawakal in the perspective of the child marriages couple. This research uses a qualitative approach. Data obtained by interview, observation and documentation. The location of the study was Wedusan Village, Tiris District, Probolinggo. The informant of the study was 24 child marriages couple. Supporting informant is parents, the community and village officials. Analysis techniques using interactive models. The results showed that tawakal attitude has been internalized in the daily life of the community, including for a couple of child marriage in the village of Wedusan. Tawakal for a couple of child marriages is a must in addressing the difficulties of life because by tawakal they surrender all risks and accept all the wishes of Allah SWT. Tawakal attitude which has been internalized in the community including a couple of child marriages was caused by low educational and economic conditions, and also the interaction patterns that are still simple and traditional. Expressions from the tawakal attitude of the community in this region, including a couple of child marriages, are expressed in gratitude and have never complained about all the conditions they experience so that even though physically (economically) they look very lacking, they are very harmonious and happy in the household. The child marriage couple in the village of Wedusan believes that their possessions are deposited from Allah SWT so that under any circumstances they continue to work and not give up. This Tawakal attitude can be categorized as an active and lofty tawakal.